Front Cover. (13th June 2019) - Feiger, Bradley; Vardhan, Madhurima; Gounley, John; Mortensen, Matthew; Nair, Priya; Chaudhury, Rafeed; Frakes, David; Randles, Amanda
Abstract : The cover image is based on the Research Article ‐ Application Suitability of lattice Boltzmann inlet and outlet boundary conditions for simulating flow in image‐derived vasculature by Bradley Feiger et al., https://doi.org/10.1002/cnm.3198 . Cover image © Liam Krauss/Lawrence Livermore National Laboratory.